Школа и педагогическая мысль Античного мира - Белокрылова Наталья Владимировна (2014)
Экземпляры: УКП (20150129) / Инвентарный номер: АП20140423 / Цена: / Сис.шифр: 74.03 / Авт.знак: Б 43 / ГРНТИ: 14.09.03 / ББК: 74.03(0)